Educational Leadership in Improving School Performance and Teacher Professional Development: A Literature Review - Pitriani, Elly (PPSDP International Journal of Education, 2024)
The purpose of this study is to examine and describe educational leadership in improving school performance and teacher professional development. This study uses a literature review approach and uses data collection methods in the form of journals and scientific articles related to research studies. The analysis used in this study includes a review of the latest research findings and screening of relevant research materials in sequence. This study reveals that educational leadership plays a role in improving school performance and encouraging teacher professional development. The instructional and distributed leadership models, as well as the professional learning community approach, show that collaboration, ongoing support, and focused professional development are key to achieving educational goals. Effective leadership not only improves teacher performance, but also contributes to improving the quality of education and student learning outcomes as a whole.